2016
DOI: 10.1002/alr.21726
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of chronic frontal sinusitis treated with ethmoidectomy: a prospective study

Abstract: Background In medically refractory chronic frontal sinusitis, ethmoidectomy without instrumentation of the frontal ostium may resolve frontal disease. Our aim was to determine the efficacy of ethmoidectomy alone for the treatment of chronic frontal sinusitis. Methods Adults with chronic rhinosinusitis prospectively enrolled in a multi-center study who demonstrated frontal sinusitis on computed tomography were divided into two groups: 1) endoscopic sinus surgery (ESS) incorporating ethmoidectomy, but excludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 25 publications
4
27
0
Order By: Relevance
“…Through EPS, using the approaches described, there is little conceivable risk of injury to the orbit or skull base. Interestingly, recent prospective data suggest that surgical treatment of ethmoid sinusitis alone may resolve frontal sinus disease without formal frontal sinusotomy . Given our findings presented herein, EPS may unexpectedly hold promise for impacting frontal sinusitis in some patients, while also avoiding the need for traditional complete ethmoidectomy under general anesthesia (and the inherent risk profiles of both interventions as previously discussed).…”
Section: Discussionsupporting
confidence: 52%
“…Through EPS, using the approaches described, there is little conceivable risk of injury to the orbit or skull base. Interestingly, recent prospective data suggest that surgical treatment of ethmoid sinusitis alone may resolve frontal sinus disease without formal frontal sinusotomy . Given our findings presented herein, EPS may unexpectedly hold promise for impacting frontal sinusitis in some patients, while also avoiding the need for traditional complete ethmoidectomy under general anesthesia (and the inherent risk profiles of both interventions as previously discussed).…”
Section: Discussionsupporting
confidence: 52%
“…Full‐length texts were then reviewed, and an additional 23 studies identified from references. A total of 31 studies were considered to be duplicates from the same cohort, and an additional 53 failed to meet inclusion/exclusion criteria. The final study list included 40 unique patient cohorts published from 2008 to 2016 and representing institutions from North America (n = 14), Europe (n = 12), Middle East (n = 6), Australia (n = 3), Asia (n = 3), and South America (n = 2) .…”
Section: Resultsmentioning
confidence: 99%
“…Becker et al found that anterior ethmoidectomy led to frontal sinus disease resolution in 89% of patients . In a group of patients with CRS and opacification of the frontal sinuses on imaging, Abuzeid et al compared those who underwent endoscopic frontal sinusotomy to those who underwent ethmoidectomy alone . They found that quality of life symptom scores and postoperative requirement for oral antibiotics improved with no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years there has been a dramatic increase (76%–153%) in the number of patients receiving frontal sinus surgery . This increase comes despite a lack of evidence supporting a frontal sinus procedure as opposed to an anterior ethmoidectomy alone as an initial surgical option for patients with frontal sinusitis on imaging …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation